2012
DOI: 10.4321/s1130-01082012000300006
|View full text |Cite
|
Sign up to set email alerts
|

Current management of gastric cancer

Abstract: Gastric cancer is a disease with high incidence and mortality in our population. The prognosis of patients with this disease is closely related to the neoplasm stage at diagnosis, including the following characteristics of the tumor: extension into the gastric wall thickness, spread to locoregional lymph nodes and the ability to generate distant metastases, as described by the TNM classification. For localized tumors characterized only by invasion of mucosa or submucosa at diagnosis, survival at 5 years is bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 62 publications
2
11
0
4
Order By: Relevance
“…This study showed promising results for EUS-FNA in the biopsy negative diffuse gastrointestinal lesions with a very high PPV reaching 100%, an NPV of 61.98%, a sensitivity of 83%, and a specificity of 100% with a p<0.0001. Our current results go hand in hand with many previous studies (12)(13)(14)(15).…”
Section: Original Articlesupporting
confidence: 81%
“…This study showed promising results for EUS-FNA in the biopsy negative diffuse gastrointestinal lesions with a very high PPV reaching 100%, an NPV of 61.98%, a sensitivity of 83%, and a specificity of 100% with a p<0.0001. Our current results go hand in hand with many previous studies (12)(13)(14)(15).…”
Section: Original Articlesupporting
confidence: 81%
“…3 These findings reveal that the choice of any chemotherapy regimen is essentially dependent upon each patient's profile. 45 Consequently, any difficulties related to currently available therapies could be surmounted via the necessary exploration of gastric cancer-specific molecular indicators. Their future incorporation in clinical practice will be expected to assist in better forecasting response to chemotherapy and general monitoring of disease outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Darüber hatten alle TNM-assozierten Kriterien ebenfalls erwartungsgemäß einen hochsignifikanten Einfluss auf das Patientenüberleben und die Rezidivhäufigkeit. In der aktuellen Novellierung der TNM-Klassifikation wurde die Perineuralscheideninfiltration als neues Kriterium hinzugefügt, auch dieser Marker erwies sich in unserer Analyse als hochsignifikanter Prognosefaktor [22]. Zahlreiche Arbeiten weisen auf die prognostische Bedeutung erweiterter pathohistologischer Prognosekriterien hin.…”
Section: Diskussionunclassified